An Analysis of Language Styles Used in Business Activities in The Founder Movie - Mochammad Feriza Machmud (UPT P2M Politeknik Negeri Malang, 2025)
In preparing vocational students for successful entry into the professional business environment, the development of pragmatic competence, particularly in the use of appropriate language styles across varied business contexts, is essential. This study examines the film The Founder as a medium for analyzing language style usage within diverse business interactions. The objectives of the study are twofold: (1) to classify business situations based on the language styles employed, and (2) to identify and analyze the factors influencing language style selection in specific business contexts. The findings are presented through a series of infographics, systematically illustrating the application of language styles across both formal and informal business activities. These infographics are designed as pedagogical resources for students of the D4 English for Business and Professional Communication program, offering authentic representations of language use in real-world business scenarios. By engaging with these materials, students are expected to enhance their communicative competence and develop the ability to select appropriate language styles in professional settings.